The Role of Digital Innovation in Improving Financial Performance in MSMEs in Indonesia - Girang Permata Gusti; Rudi Triadi Yuliarto (Journal of International Conference Proceedings (JICP), 2022)
This study aims to fill the research gap that occurs between digital orientation and digital capability on financial performance. In previous research, there are still relatively few research models on financial performance that include digital innovation in the research model, on this basis, this study tries to examine the role of digital innovation, whether it can mediate the relationship between these two variables. This research uses descriptive method with associative research design. The data collection method used is the test technique to measure the knowledge of the respondents and by distributing a questionnaire with the lingkert's scale which is selected randomly in the population with certain criteria (purposive sampling), with a total of 200 MSMEs as respondents. The result of this research is that all hypotheses are accepted. For business managers, digital innovation is an important thing to do. The more innovated, the greater the opportunity to improve the financial performance of the business being run.